Small Businesses, Big Innovations: Redefining MSE Performance Through Knowledge and Technology Synergies - Maisa Asmara; Rivaldi Arissaputra; Sherly Nur Sabila; Akbar Buchori (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The performance of MSMEs is a key priority in both developing and developed countries due to their significant economic contributions. In Indonesia, MSMEs account for 64.2 million units, contributing 61.07% to the GDP and providing employment for 135.5 million people, with the majority in the micro sector. Despite their potential, MSMEs often face challenges in management and technical skills, limiting their operational effectiveness, particularly in small-scale enterprises.Purpose: This study explores the relationship between knowledge management, technology adoption, and innovation capability in MSEs while providing practical recommendations to enhance business performance in the digital era.Design/methodology/approach: This study uses a quantitative survey approach, collecting data via Google Form and direct visits to MSME organizations. The population consists of Muslim-owned MSMEs in Bandung Raya operating for at least six months. Data were collected between November '24-January '25 from a sample of 300 respondents, and analysed using SmartPLS 4.0.Findings/Result: Knowledge management enhances innovation capability, which in turn drives technology adoption; however, none of these variables significantly affect MSEs’ performance, either directly or through mediation.Conclusion: Knowledge Management boosts Innovation Capability and Technology Adoption, but none directly enhance MSEs performance.Originality/value (State of the art): This study integrates three key concepts knowledge management, technology adoption, and innovation capability within a comprehensive and holistic research framework. Keywords:  entrepreneurship, innovation capability, knowledge management, MSEs performance, technology adoption